Comparative Metagenomics of the Polymicrobial Black Band Disease of Corals - Meyer, Julie L.; Paul, Valerie J.; Raymundo, Laurie J.; Teplitski, Max (Frontiers in Microbiology, 2017)
Black Band Disease (BBD), the destructive microbial consortium dominated by the cyanobacterium Roseofilum reptotaenium, affects corals worldwide. While the taxonomic composition of BBD consortia has been well characterized, substantially less is known about its functional repertoire. We sequenced the metagenomes of Caribbean and Pacific black band mats and cultured Roseofilum and obtained five metagenome-assembled genomes of Roseofilum, nine of Proteobacteria, and twelve of Bacteroidetes. Genomic content analysis suggests that Roseofilum is a source of organic carbon and nitrogen, as well as natural products that may influence interactions between microbes. Proteobacteria and Bacteroidetes members of the disease consortium are suited to the degradation of amino acids, proteins, and carbohydrates. The accumulation of sulfide underneath the black band mat, in part due to a lack of sulfur oxidizers, contributes to the lethality of the disease. The presence of sulfide:quinone oxidoreductase genes in all five Roseofilum genomes and several heterotrophic genomes demonstrates that resistance to sulfide is an important characteristic for members of the Black Band Disease consortium.